Perbandingan Daya Hambat Chlorhexidine Gluconate 0.2% dan Ekstrak Ethanol Bunga Kecicang (Etlingera elatior) terhadap Bakteri Staphylococcus aureus secara In Vitro - Kim Henadi; I Gusti Ayu Fienna Novianthi Sidiartha; I Gusti Agung Sri Pradnyani (Bali Dental Journal, 2021)
Introduction: Staphylococcus aureus is part of the normal human flora in the oral cavity which is often found as a pathogen in multi-cases of dental and systemic diseases. Management infection of this bacteria, generally uses β-lactam antibiotics group. However, nowadays there were often cases of Staphylococcus aureus antibiotic resistance thus Chlorhexidine gluconate (CHX) 0.2% is used. CHX has extensive antibacterial power with relatively low toxicity. Furthermore, the latest research has shown that there are even present CHX-resistant Staphylococcus aureus strains. Kecicang (Etlingera elatior) is a plant that is often used as herbs and traditional medicine in Bali. Kecicang has been shown to contain antibacterial compounds, so it is expected to be an antibacterial alternative to avoid cases of antibiotic resistance. The aim of the study is to determine the ratio of 0.2% CHX inhibition and 10%, 20%, 30%, 40%, and 50% kecicang extracts. Method: Post Test Only Control Group Design study design is used in this study, comparing the inhibitory power of kecicang flower extract with 0.2% CHX against Staphylococcus aureus (ATCC 35923). The extract is made using the maceration method, using 96% ethanol solvent, 10%, 20%, 30%, 40%, and 50% concentration then analyzed using qualitative-phytochemical analysis. The bacterial test is using the Kirby-Bauer method in MHA and observed by two examiners. Vancomycin is used as positive control and distilled water is used as a negative control. Results: Kecicang extract then detected positive for saponins, triterpenoids, steroids, phenols, and flavonoids, while alkaloids were detected negatively. The mean CHX inhibition zone is 0.2% (13,875 mm). The mean inhibition zone is 10% (5.5 mm), 20% (6 mm), 30% (6.4 mm), 40% (7.125 mm), 50% (7.5 mm). There is an increase in the inhibition zone along with increasing concentrations of kecicang extract (p <0.05) Conclusion: Based on measurements by two examiners, the kecicang flower extract 10%, 20%, 30%, 40%, and 50% has smaller inhibitory power than the 0.2% CHX inhibition power (p <0.05). Latar Belakang: Staphylococcus aureus adalah normal flora rongga mulut yang sering menjadi pathogen kasus penyakit gigi dan sistemik. Penatalaksanaan umumnya menggunakan antibiotik golongan β-laktam. Namun, dewasa ini sering dijumpai kasus resistensi Staphylococcus aureus sehingga digunakan Chlorhexidine gluconate (CHX) 0.2%. CHX memiliki daya antibakteri luas dengan toksisitas relatif rendah. Namun, penelitian menunjukan bahkan terdapat strain Staphylococcus aureus resisten CHX. Kecicang (Etlingera elatior) adalah tumbuhan yang sering dimanfaatkan sebagai rempah serta obat tradisional di Bali. Kecicang terbukti mengandung komponen fitokimia-majemuk bersifat antibakteri, sehingga diharapkan menjadi alternatif antibakteri untuk menghindari kasus resistensi antibiotik. Tujuan penelitian: mengetahui perbandingan daya hambat CHX 0.2% dan ekstrak kecicang 10%, 20%, 30%, 40%, dan 50%. Metode: Penelitian menggunakan rancangan penelitian Post Test Only Control Group Design, membandingkan daya hambat ekstrak bunga kecicang dengan CHX 0.2% terhadap Staphylococcus aureus (ATCC 35923). Ekstrak dibuat dengan metode maserasi simplisia, pelarut ethanol 96%, variasi konsentrasi 10%,20%,30%,40%, dan 50% kemudian dilakukan analisis fitokimia-kualitatif. Pengujian bakteri menggunakan metode Kirby-Bauer pada MHA, diamati dua orang mata pengamat. Kontrol positif menggunakan Vancomycin dan kontrol negatif menggunakan aquades. Hasil: Ekstrak kecicang terdeteksi positif saponin, triterpenoid, steroid, fenol, dan flavonoid, sedangkan alkaloid terdeteksi negatif. Mean zona hambat CHX 0.2% (13.875 mm). Mean zona hambat kecicang 10% (5.5 mm), 20% (6 mm), 30% (6.4 mm), 40% (7.125 mm), 50% (7.5 mm). Terlihat peningkatan zona hambat seiring dengan peningkatan konsentrasi ekstrak bunga kecicang (p<0.05) Kesimpulan: Berdasarkan pengukuran oleh dua orang mata pengamat, ekstrak bunga kecicang konsentrasi 10%,20%,30%,40%, dan 50% memiliki daya hambat lebih kecil daripada daya hambat CHX 0.2% (p<0.05).